2013
DOI: 10.1073/pnas.1217251110
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering mutant ELOVL4 activity in autosomal-dominant Stargardt macular dystrophy

Abstract: Autosomal-dominant Stargardt-like macular dystrophy [Stargardt3 (STGD3)] results from single allelic mutations in the elongation of very-long-chain fatty acids-like 4 (ELOVL4), whereas recessive mutations lead to skin and brain dysfunction. ELOVL4 protein localizes to the endoplasmic reticulum, where it mediates the condensation reaction catalyzing the formation of very-long-chain (VLC) (C-28 to C-40) fatty acids, saturated and polyunsaturated (PUFA). The defective gene product is truncated at the C terminus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 44 publications
5
77
0
Order By: Relevance
“…The leading hypotheses of STGD3 pathomechanisms are based on studies of transgenic cell cultures where ELOVL4 was expressed alone and/or in combination with the STGD3-causing mutant ELOVL4 gene (Karan et al 2005; Logan et al 2013). These studies showed that the mutant protein aggregates with the wild type version and translocates it from the ER to the cytoplasm, possibly forming aggresomes (Ambasudhan et al 2004; Karan et al 2005; Grayson and Molday 2005).…”
Section: Cell Culture Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The leading hypotheses of STGD3 pathomechanisms are based on studies of transgenic cell cultures where ELOVL4 was expressed alone and/or in combination with the STGD3-causing mutant ELOVL4 gene (Karan et al 2005; Logan et al 2013). These studies showed that the mutant protein aggregates with the wild type version and translocates it from the ER to the cytoplasm, possibly forming aggresomes (Ambasudhan et al 2004; Karan et al 2005; Grayson and Molday 2005).…”
Section: Cell Culture Studiesmentioning
confidence: 99%
“…Mutations found in STGD3 patients affect the C-terminal end of the ELOVL4 protein that contains a di-lysine motif thought to regulate protein retention within the endoplasmic reticulum (ER) (Vasireddy et al 2010). This is believed to derail proper localization of the protein to the ER, where very long chain fatty acid (VLC-FA) synthesis takes place and to suppress the biosynthetic capacity of the wild type ELOVL4 enzyme by removing it as well from the ER (Agbaga et al 2008; Guillou et al 2010; Logan et al 2013). Because ELOVL4 expression in adult vertebrate eyes is limited to the photoreceptor layer (Zhang et al 2003; Agbaga et al 2008), its VLC-PUFA products are likely to play specific but yet to be defined, functions in cones and rods (Zemski Berry et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since the ELOVL4 protein must be retained in the ER to perform its enzymatic function (Agbaga et al, 2008;Barabas et al, 2013;Harkewicz et al, 2012;Logan et al, 2014), loss of the ER-retention motif causes the ELOVL4 protein to be mislocalized within the cytosol . The mutant protein does not have any enzymatic activity of its own (Logan et al, 2013). However, using in vitro cell-based and cell-free microsomal assays, we found that coexpression of different forms of both wild-type and mutant ELOVL4 resulted in a significant dominant-negative effect of the mutant protein on both localization and enzymatic activity of the wild-type protein (Logan et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…The mutant protein does not have any enzymatic activity of its own (Logan et al, 2013). However, using in vitro cell-based and cell-free microsomal assays, we found that coexpression of different forms of both wild-type and mutant ELOVL4 resulted in a significant dominant-negative effect of the mutant protein on both localization and enzymatic activity of the wild-type protein (Logan et al, 2013). This suggests that the retina phenotype observed in STGD3 results from a loss of VLC-PUFA products due to the dominant negative effect of an enzymatically inactive mutant protein.…”
Section: Introductionmentioning
confidence: 99%
“…Since these cells are necessary for PRC functional integrity and survival, it is important to understand and unravel key signaling engaged under these conditions. We are learning that DHA is related to pivotal events for vision, which include the following: (a) DHA is the precursor of very long chain polyunsaturated fatty acids (VLC-PUFAs), which are intimately associated with rhodopsin (Aveldaño et al 1988) and remarkably decrease in content in Stargardt syndrome and in AMD (these fatty acids are made by an ELOV4-mediated elongation pathway) (Harkewicz et al 2012;Liu et al 2010;Logan et al 2013); (b) DHA is the precursor of cytoprotective, homeostasis modulator neuroprotectin D1 (NPD1; 10R,17S-dihydroxy-docosa-4Z,7Z,11E,13E,15Z,19Z-hexaenoic acid) and of other bioactive docosanoids; and (c) DHA peroxidation protein adducts evolve and accumulates in Drusen in AMD, exerting enhancing actions on its pathology (Hollyfield et al 2008).…”
Section: Photoreceptor Cell Survivalmentioning
confidence: 99%